If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + 6x + 9 = 3x + 7 + -2x + -9 Reorder the terms: -16 + 9 + 6x = 3x + 7 + -2x + -9 Combine like terms: -16 + 9 = -7 -7 + 6x = 3x + 7 + -2x + -9 Reorder the terms: -7 + 6x = 7 + -9 + 3x + -2x Combine like terms: 7 + -9 = -2 -7 + 6x = -2 + 3x + -2x Combine like terms: 3x + -2x = 1x -7 + 6x = -2 + 1x Solving -7 + 6x = -2 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -7 + 6x + -1x = -2 + 1x + -1x Combine like terms: 6x + -1x = 5x -7 + 5x = -2 + 1x + -1x Combine like terms: 1x + -1x = 0 -7 + 5x = -2 + 0 -7 + 5x = -2 Add '7' to each side of the equation. -7 + 7 + 5x = -2 + 7 Combine like terms: -7 + 7 = 0 0 + 5x = -2 + 7 5x = -2 + 7 Combine like terms: -2 + 7 = 5 5x = 5 Divide each side by '5'. x = 1 Simplifying x = 1
| y^2-4/2y+4 | | 2x/3+8/3=-2 | | 8x^3+9x^2+16x+18=0 | | 7x/8+40/8=-2 | | -5+11n=15+9n | | 3y=3y-5 | | x-0.6=8.98 | | 9+9n= | | 8-4y=7 | | 2x/5+43/5=3 | | 9(x-3)=-3(x+-4)+47 | | 7=2q-1/3(-3q+3) | | -6u=-6 | | 4(2x-3)-3(5x-1)=2(3x-24) | | -1-7=x | | 2q=3q-9 | | V^2=48 | | 4(3-5/6m)=32/3 | | 29z=-232 | | 5(x-2)=-7(x+3)+38 | | 4x/8+64/8=5 | | 80-7.94x=40.30 | | 10+7d-15=10-2d-7+5d | | 25-4y=3 | | -6r+7=4r+7 | | 3(2x+4)+2(9x-2)=2(3x+13) | | 30=8x+30 | | 4x/7+37/7=-5 | | 12-2x=-5x+18 | | 4(3-5/6m)=32/2 | | 16.95+.78x=156.57 | | 2(x+3)=6x-16 |